ASIMETRI INFORMASI MEMODERASI BEBAN PAJAK TANGGUHAN DAN MANAJEMEN LABA - Sistya Rachmawati (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The objective of this research is to ident6 the direct and indirect influences of deffered tax expense toward earning management which is moderated by asymmetry Information. This research examines 50 manufacturing companies listed in Jakarta Stock Exchange and issues auditedfinancial statement since 2004-2006. The statistical method used to test the hypothesis is Multiple Regression Model. The empirical result of this research indicates that deffered tax expense has influence to Earning Management. Test results suggest that by using the Multiple regression analysis, deffered tax expense have a direct positive significant influences to earning management, while asymmetry information have no significant influences toearning management. The control variable Cash Flow operation have positive significant influence toEarning Management, while size and growth has no significant influence Earning Management.